The Potency of Biodiesel Production from The Local Used Frying Oil Through The Electrocatalysis Method - Aulia, Haris Numan (Balai Besar Standardisasi dan Pelayanan Jasa Pencegahan Pencemaran Industri, 2023)
The objective of this study was to optimize the operating conditions for an electrocatalytic method of producing biodiesel from local used frying oil (UFO). The effects of electrical voltages (5-30 V), methanol-to-oil molar ratios (4:1-8:1), KOH catalyst concentrations (0.5-1.25% w/w), and electrolysis time (30-120 min) on biodiesel yield were investigated. The highest biodiesel yield of 95.3% was obtained at a voltage of 30 V, methanol-to-oil molar ratio of 6:1, catalyst concentration of 1% w/w, and electrolysis time of 120 min. A regression model was developed to predict the optimum operating conditions, resulting in a maximum biodiesel yield of 95.54%. The predicted optimum operating conditions were a voltage of 24.4 V, methanol-to-oil molar ratio of 5.8:1, catalyst concentration of 1% w/w, and electrolysis time of 120 min. The net profit of the biodiesel business using local UFO as a feedstock was estimated to be IDR 738,000 per month based on a simple economic calculation. These findings demonstrate the potential for using electrocatalytic methods to produce biodiesel from local UFO, and the economic feasibility of producing biodiesel in small-scale industries.